Study and analyze the results achieved from adopting and implementing the learning Strategy together to understand and comprehend the Science subject (chemistry) for the second intermediate grade - Sabri Mohammed, Afraa (International Journal of Psychosocial Rehabilitation, 2020)
The current research aims to study and analyze the results achieved from adopting and implementing a learning strategy together to understand and comprehend the science subject (chemistry) for the second intermediate grade by verifying the following null hypothesis:There is no statistically significant difference at the level of 0.05 between the average scores of the experimental group students who study the science subject according to the learning strategy together and the average scores of the control group students who study the same subject in the usual way.The research sample consisted of 44 students from the second intermediate grade, 21 students for the experimental group that studied science according to the learning strategy together, and 23 students for the control group who studied in the usual way.The researcher was rewarded between the two groups of research in the variables (age in months, previous academic achievement in the science subject for the first intermediate grade, parental achievement).The researcher prepared the teaching plans for the topics of the second and third semesters of the science textbook for the second intermediate grade.The two groups studied for a period of (4) weeks, and after completing the teaching, the achievement test was conducted for the students of the research sample, and the results indicated that there were statistically significant differences between the average achievement of students who studied science using the learning strategy together and the average achievement of students who study science in the usual way in favor of the experimental group. In light of the research findings, the researcher recommended a number of recommendations, including: 1. The constant involvement of teachers in courses, seminars, and lectures with educational goals related to modern methods of teaching.2. Training science teachers on how to use learning strategies together in teaching.3. Conducting similar studies on larger samples and in a varied study item.